Development of Real Time Operating Systen for PIC18F Microcontrollers for Educational Purposes - MOHAMED TAG ELSIR MOHAMED ELHUSSEIN, MOHAMED TAG ELSIR (Universiti Teknologi Petronas, 2009)
Real Time Operating System (RTOS) is a small operating system designed to manage the peripherals of Microcontrollers and exhibit a low level layer to enhance the parallel execution of multiple programs. In addition to that, RTOSes are most of concern about guarantee the processing at real time. This project aims to implement and develop RTOS on PIC18Fxxx family. This RTOS is to be developed under MPLAB IDE integrated development environment. The kernel of this RTOS is written in Assembly language while the users may use both assembly and C to develop their applications. A previous RTOS project called PICos18 developed by Pragamtec inc. is being considered. The selection of this system is due to its free license and the availability of its documentations. PICos18 is based on OSEK/VDX (German/French industrial standards for operating systems). The main contribution in this project is first, by developing RTOS to review and demonstrate the concept of RTOS and secondly, by developing drivers and application compatible with the developed RTOS and finally presenting the developed RTOS in educational form for future use as a teaching tool in microcontroller-based courses.